El concepto de utopía en la obra de Juan José Arreola - Buenfil Morales, Judith (Hesperia: Anuario de Filología Hispánica, 2019)
Founded on the horizon of laughter, in the work of Juan José Arreola converge the idea of an imagined prehistory, the myth of the androgyne, the thesis Freudian death drive and theories of possible matriarchal societies studied by anthropologist J. J. Bachofen. These benchmarks will serve the Mexican author to analyze the past and present of mankind, and establish an original utopian proposition.